Conference – 1992 Equation

y = α 0 + α 1 INF + α 2 VINF + ( α 3 + α 4 INF + α 5 VINF ) k + ε t MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaGaaeyEaiabg2 da9iabeg7aHnaaBaaaleaacaaIWaaabeaakiabgUcaRiabeg7aHnaa BaaaleaacaaIXaaabeaakiaabMeacaqGobGaaeOraiabgUcaRiabeg 7aHnaaBaaaleaacaaIYaaabeaakiaabAfacaqGjbGaaeOtaiaabAea cqGHRaWkdaqadaqaaiabeg7aHnaaBaaaleaacaaIZaaabeaakiabgU caRiabeg7aHnaaBaaaleaacaaI0aaabeaakiaabMeacaqGobGaaeOr aiabgUcaRiabeg7aHnaaBaaaleaacaaI1aaabeaakiaabAfacaqGjb GaaeOtaiaabAeaaiaawIcacaGLPaaacaqGRbGaey4kaSIaeqyTdu2a aSbaaSqaaiaabshaaeqaaaaa@5D38@